The Concept of Pre-Marriage Guidance in Creating a Sakinah Mawaddah Rahmah Family - Ahmad Fikram Harahap; Kamalia Kamalia (Sekolah Tinggi Agama Islam YDI Lubuk Sikaping, 2026)
This study aims to analyze the role of premarital counseling in preparing prospective brides and grooms to understand the goals of family, rights and obligations in marriage, and to achieve a sakinah, mawaddah, and rahmah family. The study used a qualitative approach with data collection techniques through interviews, observation, and documentation. The research informants numbered 5 people consisting of religious instructors, representatives of the Office of Religious Affairs (KUA), and couples who had participated in the premarital counseling program. The results of the study indicate that premarital counseling has a significant role in increasing couples' understanding of rights and obligations in the household, healthy communication, conflict management, and spiritual values ​​in fostering a family. This guidance also helps reduce divorce rates and strengthen family resilience. Thus, premarital counseling is an important instrument in realizing a sakinah, mawaddah, and rahmah family in the region[vp1]. The contribution of this study lies in presenting empirical evidence regarding the implementation of premarital counseling in the context of local Muslim communities in Indonesia. Research findings show that premarital guidance not only functions as preparation before marriage, but also as an effort to strengthen family resilience and form a sakinah, mawaddah, wa rahmah family